Recent Surgical Strategies for Rectal Cancer - Morita, T.; Itoh, T.; Nanmoku, K.; Yoshizaki, T.; Suzuki, J.; Baba, T.; Nakamura, F.; Endoh, M.; Hakamada, K.; Konn, M. (Nippon Daicho Komonbyo Gakkai Zasshi, 1996)
Recent progress of preoperative diagnostic techniques in rectal cancer has led to accurate information on spread of cancer and application of smallest necessary resection of the organ and/or the autonomic nerve and extended lymph node dissection. Widespread health screening in our country also provides more chances to treat lower-staged rectal cancer, in which organ sparing and radical lymph node dissection can be balanced. Since 1984, radical paraaortic lymph node dissection, lateral lymph node dissection though the extraperitoneal approach, and pelvic nerve and/or anus preserving operation for rectal canter have been applied. Surgical results of both subjects before and after 1984 were compared. A five-year survival rate of 83.3% of the latter cases was significantly better than that of 71.2% of former cases. Improvement was more apparent in stage IIIa cancer, and there were some long survivors with n3 or n4 degree lymph node metastases in the latter cases. Organ and/or nerve preserving operation can be consistent with radical lymph node dissection for rectal cancer, which provides both patient survival and better postoperative quality of life.